Penyertaan Modal Negara Pertumbuhan Aset Dan Kinerja Badan Usaha Milik Negara - Dinarjito, Agung (E-Jurnal Akuntansi; Vol 28 No 2 (2019)DO - 10.24843/EJA.2019.v28.i02.p20, 2019)
This study aims to examine whether State capital participation (PMN) and asset growth will affect the financial performance of State-Owned Enterprises (SOEs) in the year the addition of State capital participation. In addition, this study also examines whether PMN influences asset growth to see whether additional PMN provided by the Central Government is used to increase fixed assets in order to increase SOEs revenues. This research is a quantitative study using SOEs data in the form of a limited liability company (PT) that received PMN from 2014 to 2017. Research shows that PMN and asset growth jointly affect the performance of SOEs, but partially do not affect the performance of SOEs. In addition, PMN given by the Central Government also does not affect the growth of SOEs assets. This research can be an input for the Central Government to oversee the management of SOEs and is expected to assist the Central Government in determining which SOEs will be given additional PMN annually. Keywords : Asset growth, state capital participation, financial performance, state-owned enterprises.